Use of evidence and negotiation in the review of national standard treatment guidelines and essential medicines list: experience from Ghana. (13th November 2019) - Koduah, Augustina; Asare, Brian A; Gavor, Edith; Gyansa-Lutterodt, Martha; Andrews Annan, Edith; Ofei, Francis W
Abstract: Understanding how countries review their national standard treatment guidelines (STGs) and essential medicines list (EML) is important in the light of ever-changing trends in public health and evidence supporting the selection and use of medicines in disease management. This study examines the 2017 STGs and EML review process, the actors involved and how the list of medicines and disease conditions evolved between the last two editions. We examined expert committee reports, stakeholder engagement reports and the last two editions (2010, 2017) STGs and EML. The review process occurred in both bureaucratic and public arenas where various actors with varied power and interest engaged in ways to consolidate their influence with the use of evidence from research and practice. In the bureaucratic arena, a national medicines selection committee inaugurated by the Minister of Health assessed the 2010 edition through technical sessions considering the country's disease burden, hierarchical healthcare structure and evidence on safety and efficacy and expert opinion. To build consensus and ensure credibility service providers, professional bodies and healthcare managers scrutinized the assessed guidelines and medicines list in public arenas. In such public arenas, technical discussions moved towards negotiations with emphasis on practicability of the policies. Updates in the 2017 guidelines involved the addition of 64 new disease conditions in the STG, with the EML including 153 additional medicines and excluding 56 medicines previously found in the 2010 EML. Furthermore, the level of care categorization for Level 'A' [i.e. community-based health planning and services (CHPS)] and Level 'M' (i.e. midwifery and CHPS with a midwife) evolved to reflect the current primary healthcare and community mobilization activities for healthcare delivery in Ghana. Ghana's experience in using evidence from research and practice and engaging wide stakeholders can serve as lessons for other low and middle-income countries.